Development Of Coffee Agrotourism in Gombengsari Village, Banyuwangi Regency, East Java - Muhammad Ridla Ridla; I Nyoman Sunarta; Ni Made Sofia Wijaya (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The objective of this study was to identify the existing condition of coffee plantations as coffee agrotourism and propose a development strategy in Gombengsari Village. We chose this village because many of its residents work on coffee plantations. The approach used is qualitative and descriptive, supported by quantitative data. The data was collected through observation, focus group discussions, interviews, questionnaires, and documentation. Data analysis involved IFE, EFE, IE matrix, SWOT matrix, and QSPM. The results indicated that Gombengsari Village has great potential in component (4A) attraction, accessibility, amenities, and ancillary for agrotourism development and is supported by internal and external factors. IE matrix analysis places agrotourism development in a hold-and-maintain position, with a focus on market penetration and product development. The SWOT analysis has yielded six alternative strategies: (SO) optimization of tourism destination promotion; (WO) enhancement of human resources and facilities; (ST) optimization of cooperation between the government and the private sector; preventive measures; and (WT) improvement of safety and comfort. The QSPM analysis underscores the importance of increasing human resources as a top priority, with a TAS value of 18.24 for developing coffee agrotourism in Gombengsari Village. This indicates that Gombengsari Village has great potential to become a coffee agrotourism destination, which will boost the local economy and attract more tourists.